Development of storage box with automated and remote lock control system in WLAN environment / Muhammad Nasri Muhamad Razali, Syafnidar Abdul Halim and Mohd Hafifi Mohd Supir - Muhamad Razali, Muhammad Nasri; Abdul Halim, Syafnidar; Mohd Supir, Mohd Hafifi (College of Computing, Informatics, and Mathematics, 2024)
Traditional locks face challenges in security and efficiency, driving the demand for modern solutions like smart locks. This project addresses this need by developing a Storage Box with an Automated and Remote Lock Control System in a wireless local area network (WLAN) environment. To bolster security, the system implements MAC address filtering, restricting access to authorized devices. Users can securely control the ESP32 microcontroller and servo motors through a website, enabling remote lock/unlock functionality. Functionality, security, and performance testing were conducted, confirming the system's effectiveness in WLAN connectivity, website interactions, and microcontroller functionality. In performance testing, an unexpected result was observed, with the response time at 15 meters being less than that at 7 meters, possibly due to environmental and hardware-related factors. Latency variations were noted in different rooms within a home setting, influenced by obstacles such as walls and furniture. Future improvements could include exploring advanced encryption protocols or alternative authentication methods to enhance security against evolving threats like MAC address spoofing.